Latent value in humiliation: A design thinking tool to enhance empathy in creative ideation. Issue 1 (2nd January 2022) - Svihla, Vanessa; Kachelmeier, Luke
ABSTRACT: Design thinking emphasizes that in addition to being creative, design solutions should be empathetic. Yet, research suggests there may be a tension between these goals, where focusing on empathy comes at a cost to creativity, sometimes by inducing fixation. We investigated this phenomenon through a quasi-experimental design with novice designers, contrasting two structured ideation techniques in which participants (N = 47) generated bad ideas prior to proposing beneficial ideas. Specifically, they used the wrong theory protocol (WTP) to generate harmful and humiliating ideas, and a variant in which they instead generated silly and impossible ideas (SIP). We used qualitative analysis to characterize their bad and beneficial ideas. Across two realistic design challenges, we found students' initial bad design work was shaped by the technique they used, and that those who generated humiliating ideas were more likely to generate empathetic beneficial ideas afterward. No systematic differences were found in the breadth of solution ideas, suggesting this technique does not come at a cost to creativity. As a quick and easy-to-use technique, generating humiliating ideas prior to generating beneficial ideas holds promise as a means to reach design solutions that are both empathetic and creative.